Konsep Pendidikan Birrul Walidain Perspektif Q.S Al-Luqman Ayat 13-14 - Sri Nurhidayah; Waharjani Waharjani; Djamaluddin Perawironegoro (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
This research is aimed at discussing the concept of education from the Birrul Walidain perspective Q.S. Al-Luqman, paragraphs 13–14. Birrul walidain is a praise to both parents. In the Qur'an, Allah has revealed many signs concerning Birrul Walidain. One of them is in Luqman's letter, verses 13 and 14. The purpose of this study is to convey or recall the struggle of parents in caring for and nurturing their children and considering the importance of instilling morality in their children as early as possible. This method of research uses library research, better known as librarian research. The results of this study can be used as examples for children in the present and future to always apply the contents of Al-Luqman verses 13–14.